Neck Circumference: A Novel Anthropometric Tool for Screening Obesity Among Young Adults - Mouna Hogalagere Sriramappa; Hamsa Lokanath; Jai Krishna Madarakkal Gunaseelan; Chittem Sravana Deepthi; Anu Priya Mathew Chirakkara; Tapasi Lahari Reddy (National Journal of Community Medicine, 2024)
Background: Obesity is a global health concern characterized by excessive fat accumulation, posing significant health risks that affect all age groups. Particularly among young adults, including medical students, obesity can lead to physical and psychosocial consequences, emphasizing the need for effective screening. The study was conducted to evaluate the effectiveness of using neck circumference as a screening tool for detecting obesity among young adults by assessing its correlation with other anthropometric measurements and determining the appropriate cut-off points